Kebutuhan informasi dari ibu menyusui dalam program “Perbaikan Gizi: ASI Eksklusif” - Fadhila Nurul Husna Zalmi (Program Studi Diploma Tiga Ilmu Perpustakaan Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2018)
This study refers to the results of previous studies that have been conducted that aims to determine the response to health information needs of breastfeeding mothers in nutrition improvement programs: exclusive breastfeeding consisting of cognitive information needs, affective needs, personal integration needs, social integration needs, and imaginary needs. The theory used in this study is the SOR theory (stimulus-organism-response). The method used in this research is literature research method. Where this article discusses more in the health information needs of breastfeeding mothers who attend a nutrition improvement program at the Thursday Thursday West Sumatra Health Center. Cognitive information needs and affective information needs for breastfeeding mothers are good. In addition, the fulfillment of personal integration information needs and the fulfillment of social integration needs for breastfeeding mothers are already very good and for imaginary needs is good for breastfeeding mothers. It can be concluded that the information needs for breastfeeding mothers who participate in nutrition improvement counseling programs: this exclusive breastfeeding has been fulfilled.